Ancient DNA shows high faunal diversity in the Lesser Caucasus during the Late Pleistocene - Antonosyan, M.; Seersholm, Frederik; Grealy, Alicia; Barham, Milo; Werndly, Daniel; Margaryan, A.; Cieślik, A.; Stafford, T.W.; Allentoft, M.E.; Bunce, Michael; Yepiskoposyan, L. (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
© 2019 Elsevier Ltd In this study, we explore the Late Pleistocene (LP) vertebrate faunal diversity in south-eastern Lesser Caucasus based on morphological and genetic identification of fossil bones from Karin Tak cave. For the first time in this under-studied region, we used a bulk bone metabarcoding genetic approach to complement traditional morphology-based taxonomic identifications that are hampered by highly fragmented fossil bones. Excellent ancient DNA (aDNA) preservation allowed for a successful species identification of many bone remains and improved paleoenvironmental interpretations for the region. The aDNA identification of fossil bones revealed a high diversity of animal taxa inhabiting the region between ca. > 42,000 and 25,683–24,803 calibrated years before present (cal. BP).